Natural Disasters and Women Entrepreneurs During the Covid-19 Pandemic in Indonesia - Nur Asrofi, Dien Amalina; Pratomo, Devanto Shasta; Pangestuty, Farah Wulandari (Asia Pacific Journal of Management and Education (APJME), 2023)
The Covid-19 Pandemic is affecting different social groups. One of them is a woman. To help save the family's economy, women try to increase their income through entrepreneurship. However, Indonesia was also surprised by the number of occurrences of natural disasters in various regions. This study aims to examine how the impact of natural disasters that occur with disaster risk on the participation of women entrepreneurs. Simultaneously, this is exacerbated by the Covid-19 Pandemic which has an impact on the state of women entrepreneurs. The method used is binary logistic regression followed by the Heckman model for income analysis. Using the Disaster Risk Index data from BNPB and the 2020 National Labor Force Survey (Sakernas) data, this study found that natural disasters encourage the participation of women entrepreneurs and cause income to decline due to natural disasters and the Covid-19 Pandemic. Moreover, internet use has helped women entrepreneurs increase their income in post-disaster conditions and the Covid-19 Pandemic in Indonesia.